Postharvest responses of cut Dendrobium orchids to exogenous ethylene - Almasi, Parviz; Tengku Muda Mohamed, Mahmud; Ahmad, Siti Hajar; Kadir, Jugah; Mirshekari, Amin (Academic Journals, 2012)
The time to senescence of flowers in Dendrobium hybrids is different and one of the major reasons for this variation in vase life can be related to differences in the level of ethylene sensitivity. This study was conducted to determine the sensitivity of six cutDendrobium hybrids to exogenous ethylene. The cut orchid inflorescences were treated with or without 10 µL/L ethylene gas for 24 h, and then placed in bottles containing a standard vase solution. Water loss, vase life, anthocyanin contents and ethylene production were determined after the treatments. The results indicated that different hybrids showed distinct variances in ethylene sensitivities and degrees of deterioration. Dendrobium ‘Darren Glory’ and D. ‘Jaquelyne Concert’ × D. ‘Rinappa’ exhibited the utmost hyponasty, weight loss and degradation of anthocyanin content in sepals and petals. Thus, these two hybrids were categorized as the very sensitive group. On the other hand, D. ‘Sonia Red’, D. ‘Shavin White’, D. ‘Sonia White’ and D.‘Sonia Bom’ showed lower sensitivity and hence were categorized in the less sensitive group. The results of this experiment and similar experiments to determine the resistant and susceptible cultivars to ethylene injury can be helpful in improving the postharvest life of cut orchid flowers.